2014
DOI: 10.1002/asi.23147
|View full text |Cite
|
Sign up to set email alerts
|

Shared files: The retrieval perspective

Abstract: People who are collaborating can share files in two main ways: performing Group Information Management (GIM) using a common repository or performing Personal Information Management (PIM) by distributing files as e-mail attachments and storing them in personal repositories. There is a trend toward using common repositories with many organizations encouraging workers to use GIM to avoid duplication of files and management. So far, PIM and GIM have been studied by different research communities, so their effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 73 publications
8
54
5
Order By: Relevance
“…Users may file every single document despite each classification action being cognitively demanding (Ravasio et al, 2004), or may leave up to 6.5% unfiled (Henderson & Srinivasan, 2011), sometimes called dumping, perhaps because they are unsure where to put a file, do not have time to file it, or want it to be easily accessible (for example, on the desktop; Kamaruddin & Dix, 2010). Depending on the user, filing the average file may mean storing it just two levels down from the root of the tree (Bergman, Whittaker, & Falk, 2014), whereas others store most files in deeper levels (Hicks et al, 2008). As the number of files in a folder increases, so does the work required to review them all, and although users report creating new subfolders when a folder contains 3 to 7 items (Ravasio et al, 2004), the average number of files found in folders has ranged from low figures such as 0 (Henderson & Srinivasan, 2009) or 4 (Zhang & Hu, 2014) to 12 (Bergman et al, 2010;Henderson & Srinivasan, 2009) or 16 (GonQalves & Jorge, 2003Hardof-Jaffe, Hershkovitz, Abu-Kishk, Bergman, & Nachmias, 2009b).…”
Section: Understanding User Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Users may file every single document despite each classification action being cognitively demanding (Ravasio et al, 2004), or may leave up to 6.5% unfiled (Henderson & Srinivasan, 2011), sometimes called dumping, perhaps because they are unsure where to put a file, do not have time to file it, or want it to be easily accessible (for example, on the desktop; Kamaruddin & Dix, 2010). Depending on the user, filing the average file may mean storing it just two levels down from the root of the tree (Bergman, Whittaker, & Falk, 2014), whereas others store most files in deeper levels (Hicks et al, 2008). As the number of files in a folder increases, so does the work required to review them all, and although users report creating new subfolders when a folder contains 3 to 7 items (Ravasio et al, 2004), the average number of files found in folders has ranged from low figures such as 0 (Henderson & Srinivasan, 2009) or 4 (Zhang & Hu, 2014) to 12 (Bergman et al, 2010;Henderson & Srinivasan, 2009) or 16 (GonQalves & Jorge, 2003Hardof-Jaffe, Hershkovitz, Abu-Kishk, Bergman, & Nachmias, 2009b).…”
Section: Understanding User Behaviormentioning
confidence: 99%
“…Observation is a popular approach to investigating fine-grained phenomena and specific challenges in FM. Studies using this approach have, for example, sought to understand if digital documents are organized like paper documents (Barreau, 1995), how information from the web is stored in files (Jones et al, 2001;2002), and various challenges of file retrieval (Bergman et al, 2014). This is typically done by recording participants as they perform ordinary work, prompted retrieval tasks (for example, elicited personal information retrieval or EPIR tasks as in Bergman et al, 2018, among others), or a guided tour (Thomson, 2015), where they navigate and explain their folder arrangement to an observer and perform common FM tasks along the way.…”
Section: System Augmentation Studiesmentioning
confidence: 99%
“…Personal content sharing may be embedded in activities or applications used for two, often interrelated, tasks: personal information management, or "personally organizing" one's files, for example for synchronization across devices, and group information management, managing files in a collaborative setting such as a repository system (e.g., Dropbox, Google Drive) [1]. To choose channels for information management, users tend to consider content size, privacy and security, institutional policy, service accessibility and usability, and group familiarity with systems [4,30,32].…”
Section: Information Managementmentioning
confidence: 99%
“…For example, when choosing between cloud storage and email for file management, people tended to choose email for its perceived reliability, simplicity, broad access, and level of control. They chose cloud systems because of organizational policy, broad reach, novelty, and the ability to collaborate and share large files [1,25].…”
Section: Information Managementmentioning
confidence: 99%
“…As our results can be regarded as counterintuitive, we retested them by conducting a combined data analysis. We combined our data with the data from our previous studies which also tested shared files retrieval using EPIR (Bergman, Whittaker, & Falk, 2014;Bergman, Whittaker, & Frishman, 2019;Bergman & Yanai, 2017). Altogether, we examined data regarding the actual retrievals of 653 participants.…”
Section: Rq2: How Does Age Affect Search Percentage?mentioning
confidence: 99%